Systematic Literature Review: Independensi Komite Audit, Keberagaman Gender dalam Dewan, dan Kepemilikan Institusional terhadap Pengungkapan ESG - M. Saiful Rizal; Merlin Diva Mefia; Firman Ramadhani; Dien Noviany Rahmatika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to provide a more comprehensive understanding of the influence of independent audit committees, board gender diversity, and institutional ownership on Environmental, Social, and Governance (ESG) disclosure among companies in Indonesia. Using a Systematic Literature Review (SLR) method, a total of 40 articles published between 2021 and 2025 were reviewed based on thematic relevance, methodological rigor, and their contribution to the literature on sustainable corporate governance. The findings indicate that independent audit committees consistently strengthen the effectiveness of oversight and enhance the quality, transparency, and credibility of ESG reporting. Board gender diversity is shown to broaden strategic perspectives, increase sensitivity to sustainability issues, and encourage greater corporate accountability in reporting practices. Meanwhile, institutional ownership presents mixed findings; however, strong or diversified ownership structures are found to increase monitoring pressure on management. Overall, this study confirms that corporate governance mechanisms play a crucial role in improving the quality of ESG disclosure and reinforcing corporate commitment to sustainable practices in Indonesia.